Minding the (Age) Gap: The Identity and Emotion Work of Men and Women in Age-Discrepant Romantic Relationships. Issue 1 (2nd January 2021) - Niccolai, Ashley; Swauger, Melissa
ABSTRACT: People involved in an age-discrepant relationship, where one partner is significantly older than the other, are typically viewed with negative cultural tropes and stereotypes. Using a chain sampling technique to recruit participants, data were collected through 20 in-depth interviews with men and women who experienced being in a relationship with an age gap of 10 or more years between partners. Analyses revealed participants used common techniques to manage and overcome the stigma, both in self-interaction and in interaction with others. In self-interaction, participants drew from "love narratives" to reframe their involvement with someone much younger or older as something outside of their control. When interacting with others, participants used techniques of passing, lampooning, and dismissing. Passing involved participants' ability to feel and appear closer in age to their partner. Lampooning involved the use of humor to deflect the threat of stigma. Dismissing involved repudiation of the stigma associated with age-discrepant relationships. Importantly, participants' use of these techniques worked either in defense of or as a reaction against the inequality they faced in an age-discrepant relationship.